Mindfulness Practice as a Means to Increase Happiness and Enhance Service Employees’ Work Performance in Hotels/Resorts in Southern Thailand - Sirirat, Boonyapak; Dowpiset, Kitikorn (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
The objective of this study is to present the improvement of employees’ work performance in the hospitality industry in Thailand after mindfulness implementation, including some successful cases and factors contributing towards better work performance. A qualitative approach was applied to this research based on observations of all employees (n=50) through an "Open Space/Marketplace" workshop and interviews of all supervisors and some randomly selected employees (n = 22) according to their availability. The findings identified 3 major areas of improvement: participation in terms of communication; patients’ understanding; and prioritization (planning). The study focused on all employees working at the organization. The results show how mindful practices can be used in an organization and how they can help people change in certain ways. This leads to better team performance and big improvements in the organization’s overall performance